Zorba the Buddha : sex, spirituality, and capitalism in the global Osho movement - Urban, Hugh B. (Oakland, California : University of California Press, 2015)
"Zorba the Buddha is the first comprehensive study of the life, teachings, and following of the controversial Indian guru known in his youth as Bhagwan Shree Rajneesh and in his later years as Osho (1931-1990). Most Americans today remember him only as the "sex guru" and the "Rolls Royce guru," who built a hugely successful but scandal-ridden utopian community in central Oregon during the 1980s. Yet Osho was arguably the first truly global guru of the twentieth century, creating a large transnational movement that traced a complex global circuit from the post-Independence India of the 1960s to Reagan's America of the 1980s and back to a developing new India in the 1990s. The Osho movement not only reflects but critically embodies some of the most important economic and spiritual currents of the last forty years, emerging within and adapting to an increasingly interconnected and conflicted late-capitalist world order. Based on extensive ethnographic and archival research, Hugh Urban has created a rich and powerful narrative that is a must-read for anyone interested in religion and globalization"--Provided by publisher.
Introduction : gurus, god-men and globalization -- "India's most dangerous guru" : Rajneesh and India after independence -- "Beware of socialism!" : the "anti-Gandhi" and the early Rajneesh community in the 1970s -- "From sex to superconsciousness" : sexuality, Tantra, liberation in 1970s India -- "The messiah America has been waiting for" : Rajneeshpuram in 1980s America -- "Osho" : the apotheosis of a fallen guru in 1990s India -- Osho (r)? the struggle over Osho's spiritual, national, legal and financial legacy in the twenty-first century -- Conclusions : Osho's legacy : the spiritual logic of late capitalism.
Includes bibliographical references and index.
Print version record.
Keywords: Osho, -- 1931-1990.; Osho, -- 1931-1990.; Gurus -- Biography; New Age movement -- Oregon -- History -- 20th century; New Age movement -- India -- History; Gurus; New Age movement; India; Oregon; BIOGRAPHY & AUTOBIOGRAPHY / General; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; RELIGION / Hinduism / General; Biography; History; Electronic books; Electronic books